Tarekat and Work Ethos of Muslim Businesses (Study of Work Ethics Based on Sufism) - Ivan Rahmat Santoso (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2020)
This paper examines the role of the tarekat as a spiritual means of getting closer to Allah SWT, and how to significantly influence the work ethic of entrepreneurs, based on Sufism values. The method used in this study is library research. It aims to constructively analyze the contributions and role of the teachings of the tarekat towards the work ethic of the business entrepreneurial behaviour of its followers. This result showed that the tarekat, as a remembrance or recollection of God, purifies the soul from despicable acts. It birthed the characteristics of work ethic in accordance with Islamic teachings, such include optimism, Istiqamah, Wara’, Ikhlas, Rida and Qana'ah. In addition, Ihsan attitude as a tarekat source has an impact on the behaviour of entrepreneurs to always be honest and trustworthy in improving the quality of their economy.